Catalytic combustion of propane over Mg-modified Co1.5Mn1.5O4 spinel catalysts: Boosting C-H cleavage with Lewis acid and oxygen vacancies. (1st May 2023) - Zhang, Chi; Lan, Yubei; Cao, Yijia; Tang, Shengwei; Chen, Yunfa; Tang, Wenxiang
Graphical abstract: Highlights: The incorporation of Mg into Co1.5 Mn1.5 O4 spinel catalysts can greatly enhance its activity for propane combustion. The modification of Mg lead to the generation of higher metal oxidation state species and oxygen vacancies. The enhanced activity was originated from higher content of Mn 4+, Co 3+ and oxygen vacancies. Abundant Lewis acid-base pairs could boost the dissociation adsorption of propane. Abstract: Rational modulation of surface electronic structure can optimize the adsorption and activation of reactant molecules on the catalyst surface, which is crucial for catalytic elimination of hydrocarbons. Herein, a facile low-valence Mg doping strategy was applied to synthesize highly active and stable Co-Mn binary oxide (CMO) catalyst. Lewis acid sites and oxygen vacancies were purposefully introduced on CMO through the surface electron deficit caused by the substitution of doped Mg for host metals. For the CMO catalyst modified by appropriate amount of Mg (CMO-Mg0. 05 ), the Co-Mn spinel with lattice expansion is significantly modified through substitution of Co or Mn ions with Mg 2+, resulting in generation of abundant higher metal oxidation state species (Co 3+, Mn 4+ ) and oxygen vacancies. The best performance for catalytic propane combustion was achieved on CMO-Mg0. 05 catalyst, with the T90 at 255 °C under high space velocity (60, 000 ml g −1  h −1 ). Meanwhile, clear improvements on stability and water resistance were also achieved after the modification of Mg in CMO catalyst. Combined with C3 H8 -TPD, in-situ DRIFTS and various characterizations, it can be revealed that the synergistic effect of Lewis-acid sites and oxygen vacancies would remarkably promote the process of propane dissociative adsorption and mineralization. This work not only gives insight into the Mg dopants in boosting CH activation on CMO catalyst, but also provides a potential strategy for fabricating highly active hydrocarbon combustion catalysts.